2019
DOI: 10.1111/cns.13103
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal composition of gut microbiota contributes to delirium‐like behaviors after abdominal surgery in mice

Abstract: Summary Aims Anesthesia and surgery can cause delirium‐like symptoms postoperatively. Increasing evidence suggests that gut microbiota is a physiological regulator of the brain. Herein, we investigated whether gut microbiota plays a role in postoperative delirium (POD). Methods Mice were separated into non‐POD and POD phenotypes after abdominal surgery by applying hierarchical clustering analysis to behavioral tests. Fecal samples were collected, and 16S ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 35 publications
2
40
0
3
Order By: Relevance
“…Next, we investigated the composition of the gut microbiota, which can be altered by antibiotic cocktail treatment [3335], in the four experimental groups. α-diversity is defined as the richness of gut microbiota and can be measured using different indices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we investigated the composition of the gut microbiota, which can be altered by antibiotic cocktail treatment [3335], in the four experimental groups. α-diversity is defined as the richness of gut microbiota and can be measured using different indices.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, although antibiotics are crucial, their overuse plays a role in the pathogenesis of several diseases associated with microbiota impairment [24, 25]. Antibiotic cocktail-induced microbiome depletion has been used to investigate the role of gut microbiota in some pathological conditions [2635]. In addition, Sampson et al .…”
Section: Introductionmentioning
confidence: 99%
“…After checking the original data, we concluded that SPT results were more constant than the others, suggesting SPT may be a major factor of the clustering results. Next, our previous study (Zhang et al, 2019) indicated that postoperative delirium was at high risk during early-stage after surgery and anesthesia, in which emotional disorder, such as depression, occurred frequently in clinics (Samuelsson et al, 2007;Costigan et al, 2009;Patel and Sun, 2009). Hence, behavioral tests at early timepoints were suitable to be employed to observe the depressionlike symptoms in mice.…”
Section: Discussionmentioning
confidence: 96%
“…This microbial dysbiosis is closely linked to disturbances of gene expression of inflammatory cytokines. It has been documented that abnormal intestinal microbiota composition may be an important risk factor of postoperative delirium [ 93 ]. An experimental study has shown an elevated amount of Escherichia and Shigella in animals with delirium [ 94 ].…”
Section: Gut Microbiota Dysregulationmentioning
confidence: 99%